Influence of Reproductive Rhythm and Weaning Age on Fertility and Body Condition of Local Breed Does in the District of Abidjan - Kouhana, Soro; Brahima, Soro; Kpandji Isidore, Kouadio; Didier Paulin, Sokouri; Bosson Austin, Nguetta; M’Betiegue, Coulibaly; Assanvo Simon-Pierre, N’Guetta Assanvo Simon-Pierre (European Scientific Journal, ESJ, 2020)
The objective of this study is to evaluate the reproductive performance of locally bred rabbits by comparing the production of females mated 11 days postpartum (semi-intensive R42) with those mated 25 days postpartum (extensive rhythm R56). Females are naturally protruding.120 rabbits selected from a private farm in Bingerville in the district of Abidjan were followed during the experiment. Receptivity and gestation rates were not significantly influenced (p>0.05) by the reproductive rhythm in the breeding females. Fertility in multiparous females showed a higher rate in the extensive rhythm (89-100%). The semi-intensive rhythm had the highest stillbirth rate (5.6%) and pre-weaning morbidity (14.03%). However, after weaning, morbidity was higher in bunnies in the extensive rhythm (13.6%). In the extensive rhythm, the highest values were observed for the number of weaned bunnies and the survival rate of breeding females. The extensive rhythm significantly increases the longevity of does with a high mortality rate of bunny rabbits. These results could be indicators for further investigation in the search for an optimum rate of rabbit reproduction.